Writing dialogue for scripts - Davis, Rib (Writing handbooks, 2016)
"Including new case-study examples from shows and films such as Breaking Bad, Girls and In Bruges, this is a fully updated new edition of the bestselling guide to writing dialogue for stage, television, radio and film"--Provided by publisher.